S38 Omicron (B.1.1.529) SARS-CoV-2 infection results in less severe disease than infection with Delta (B.1.1.617.2) variant among hospitalised adults: a prospective cohort study. (11th November 2022) - Hyams, C; Challen, R; Marlow, R; Nguyen, JL; Begier, E; Southern, J; Morley, A; King, J; Kinney, J; Clout, M; Oliver, J; Ellsbury, G; et al.
Abstract : Background: Limited data exist assessing severity of disease in adults hospitalised with Omicron SARS-CoV-2 variant infection, and to what extent patient-factors, including vaccination and pre-existing disease, affect variant-dependent disease severity. Understanding disease severity and treatment requirements of new variants is important for hospital service and public health planning. Methods: This prospective cohort study of adults (≥18 y) hospitalised with acute respiratory illness in secondary care in Bristol, UK during June 2021–March 2022 assessed disease severity following admission with Omicron or Delta infection using three different measures: FiO2 >28%, World Health Organization (WHO) outcome score >5, and hospital length of stay (LOS) >3 days. Multivariable Poisson regression models with robust error variance adjusted for patient demographics, clinical characteristics, and calendar time were used to estimate the relative risk (RR) of each outcome. Results: Patients hospitalised with Omicron infection (n=748) were significantly older than those with Delta (n=1190) infection (median: 70·6 y vs 57·7 y; P <0.001) and had a higher median Charlson Comorbidity Index (4 vs 2; P <0·001). Independent of other variables, including COVID-19 vaccination, Omicron infection was associated with significantly lower severity compared to Delta across all three severity scores (58% lower for FiO2 [RR = 0·42 (95% CI: 0·34–0·52)], 67% lower for WHO score [RR = 0·33 (0·21–0·50)], and 16% lower for LOS [RR = 0·84 (0·76–0·92)]. In analyses stratified by vaccination status, infection with Omicron relative to Delta was associated with lower severity across all three severity measures for both vaccinated and unvaccinated patients. Compared to unvaccinated patients, vaccinated (two doses) individuals were less likely to require FiO2 >28% [RR=0·78 (0·68–0·89)], positive-pressure ventilatory support or increased critical care [RR=0·56 (0·43–0·73)], and to have LOS>3 days [RR=0.90 (0·84–0·98)]. Conclusions: Omicron infection was associated with less severe illness compared to Delta infection across three separate measures of severity. COVID-19 vaccination was independently associated with lower in-hospital disease severity, regardless of variant. Lower severity of Omicron combined with the ability of vaccine to further reduce severity may result in reduced pressure on healthcare services; however, the increased transmissibility of Omicron and potential for higher numbers of infections, particularly in elderly patients, may mitigate these benefits. Please refer to page A208 for declarations of interest related to this abstract.